Exchange protein directly activated by cAMP 1 promotes autophagy during cardiomyocyte hypertrophy. (19th November 2014) - Laurent, Anne-Coline; Bisserier, Malik; Lucas, Alexandre; Tortosa, Florence; Roumieux, Marie; De Régibus, Annélie; Swiader, Audrey; Sainte-Marie, Yannis; Heymes, Christophe; Vindis, Cécile; Lezoualc'h, Frank
Abstract: Aims: Stimulation of β-adrenergic receptors (β-AR) increases cAMP production and contributes to the pathogenesis of cardiac hypertrophy and failure through poorly understood mechanisms. We previously demonstrated that Exchange protein directly activated by cAMP 1 (Epac1)-induced hypertrophy in primary cardiomyocytes. Among the mechanisms triggered by cardiac stress, autophagy has been highlighted as a protective or harmful response. Here, we investigate whether Epac1 promotes cardiac autophagy and how altered autophagy has an impact on Epac1-induced cardiomyocyte hypertrophy. Methods and results: We reported that direct stimulation of Epac1 with the agonist, Sp-8-(4-chlorophenylthio)-2′- O -methyl-cAMP (Sp-8-pCPT) promoted autophagy activation in neonatal cardiomyocytes. Stimulation of β-AR with isoprenaline (ISO) mimicked the effect of Epac1 on autophagy markers. Conversely, the induction of autophagy flux following ISO treatment was prevented in cardiomyocytes pre-treated with a selective inhibitor of Epac1, CE3F4. Importantly, we found that Epac1 deletion in mice protected against β-AR-induced cardiac remodelling and prevented the induction of autophagy. The signalling mechanisms underlying Epac1-induced autophagy involved a Ca 2+ /calmodulin-dependent kinase kinase β (CaMKKβ)/AMP-dependent protein kinase (AMPK) pathway. Finally, we provided evidence that pharmacological inhibition of autophagy using 3-methyladenine (3-MA) or down-regulation of autophagy-related protein 5 (Atg5) significantly potentiated Epac1-promoted cardiomyocyte hypertrophy. Conclusion: Altogether, these findings demonstrate that autophagy is an adaptive response to antagonize Epac1-promoted cardiomyocyte hypertrophy.